Work status among middle-aged and older individuals in China: the effects on physical and mental health - Fu, Yi; Li, Xiaohan (Frontiers in Public Health, 2024)
Objective: China's middle-aged and older population is a rich source of human capital. Therefore, considering the health of this group is important when creating and using human resources. Methods: Using data from the nationwide China Health and Retirement Longitudinal Study (CHARLS) 2018 baseline survey of 19,000 adults ages 45 years and older, this study was an objective investigation of the effects of work on the physical and mental health of middle-aged and older adults. We conducted several types of analyses using details of participants’ lifestyles and demographic characteristics (living environment, education, financial level, and access to medical services) with work (i.e., employment or volunteer work) as a primary input component of health production to examine their effects on the health status of middle-aged and older individuals. Results: Six primary outcomes were identified: (1) Employment positively affects both the physical and mental health of middle-aged and older people; (2) Employment can influence the physical and mental health of middle-aged and older people through income, cognitive level, and social support networks; (3) Compared to non-self-employment, self-employment dramatically worsens physical health but has no apparent detrimental effects on mental health. Compared to non-agricultural employment, agricultural labour affects both physical and mental health. (4) Employment has more positive physical and mental health effects in Individuals with higher rather than lower levels of education. (5) Employment opportunities in the eastern region are more likely to promote better physical health than those in the central and western regions of China, although the effects on mental health are negative. (6) When considering groups at different ages of the lifespan, the 60–65-year-old group, who are just entering retirement probably benefit more from continuing work. Conclusions: We provide some recommendations to encourage middle-aged and older people to work and utilise their experience, which will enhance their physical and mental well-being and help them in realise their own value and social integration.